Womens participation in rice mills in Sherpur sadar upazila of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2014)
The main purpose of this study was to determine womens participation in rice mills of Sherpur sadar upazila of Bangladesh. Ninety respondents were selected using cluster random sampling method. The researchers personally collected data from August to September 2012. Aimed at explaining the assessment of the present status of women worker of rice mills and explored the relationship between their selected characteristics and extent of participation. Majority of the respondents had long experience in working in the rice mill and almost everybody had participation around the year. Women were mostly involved in drying and on an average spent time for helping in husking machine operating (3.02 hours) followed by final drying of paddy (2.05 hours), drying the paddy before boiling (1.25 hours), piling the paddy (1.12 hours), cleaning the threshing floor (1.05 hours), packing the rice (1.02 hours) per day. They worked about 8-10 hours per day. Results show that the women workers performance decreased with the increase of their age. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.21089 Int. J. Agril. Res. Innov. & Tech. 4 (1): 36-39, June, 2014